Disruption of Cesarean Scar with Uterovesical Space Hematocele Mimicking an Endometrioma - Sujata Datta; Ritisha Basu (Mary Ann Liebert, 2022)
Our case highlights an extreme form of cesarean scar defect with diagnostic and surgical challenges. The unusual presentation of a large extrauterine-encapsulated collection of altered blood and hemosiderin behind the posterior bladder wall that communicated with the endometrial cavity, through a full thickness myometrial discontinuity, at the site of a previous cesarean section, mimicked an endometrioma in an unusual location. This case report not only highlights the diagnostic challenge involved in this case but also highlights the surgical steps involved in the laparoscopic management of this extreme end of the spectrum of cesarean scar defects. We have attached a video of the laparoscopic surgery with step-wise description to shed more light on the management of this rare complication.